2020
DOI: 10.1002/bjs.11511
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of liver surface nodularity for preoperative risk assessment in patients with resectable hepatocellular carcinoma

Abstract: Background: Quantification of liver surface nodularity (LSN) on routine preoperative CT images allows detection of cirrhosis and clinically significant portal hypertension. This study aimed to assess the relevance of LSN in preoperative assessment of operative risks for patients with resectable hepatocellular carcinoma (HCC).Methods: All patients undergoing hepatectomy for HCC between 2012 and 2017 were analysed retrospectively. LSN was assessed at the liver-fat interface on the left liver lobe on preoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…This means that less than half of HCC patients experienced an ideal outcome following LR, and emphasises that HCC patients are likely to develop postoperative complications related to underlying cirrhosis. 33,34 This study highlights the pivotal prognostic role of having an ideal outcome following LR. All TO criteria are separately acknowledged to influence the prognosis of HCC patients.…”
Section: Discussionmentioning
confidence: 78%
“…This means that less than half of HCC patients experienced an ideal outcome following LR, and emphasises that HCC patients are likely to develop postoperative complications related to underlying cirrhosis. 33,34 This study highlights the pivotal prognostic role of having an ideal outcome following LR. All TO criteria are separately acknowledged to influence the prognosis of HCC patients.…”
Section: Discussionmentioning
confidence: 78%
“…Noticeably, our group recently showed that the preoperative LSN value was associated with severe complications, postoperative liver failure, and clinically significant postoperative liver failure in patients with HCC undergoing resection. 27 In addition, there was no external validation cohort. Nevertheless, our study further validates the results of Sartoris et al 10 Finally, no sample size calculation was performed.…”
Section: Criterionmentioning
confidence: 99%
“…Its performance as also found to be similar to LSM in patients with HCC with a two‐step algorithm combining LSN and LSPS, resulting in accurate detection of clinically‐significant portal hypertension in more than 75% of patients 26 . Finally, this simple quantitative biomarker was shown to be a practical tool for the assessment of preoperative risk in patients with resectable HCC, with a better performance than the usual liver function tests such as the MELD score, APRI and FIB‐4 score 27 . As for radiomics, LSN measurement is retrospectively performed on routine cross‐sectional images, making it easier to transfer these results from research to clinical reality.…”
Section: Examples Of Advances As a Results Of Quantitative Models For Hepatocellular Carcinomamentioning
confidence: 65%